2014
DOI: 10.1016/j.jcmg.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Additional Value of Transluminal Attenuation Gradient in CT Angiography to Predict Hemodynamic Significance of Coronary Artery Stenosis

Abstract: OBJECTIVES The current study evaluates the incremental value of transluminal attenuation gradient (TAG), TAG with corrected contrast opacification (CCO), and TAG with exclusion of calcified coronary segments (ExC) over coronary computed tomography angiogram (CTA) alone using fractional flow reserve (FFR) as the gold standard. BACKGROUND TAG is defined as the contrast opacification gradient along the length of a coronary artery on a coronary CTA. Preliminary data suggest that TAG provides additional functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 36 publications
2
62
1
Order By: Relevance
“…Therefore, abnormality by TAG is likely to be associated with severe anatomic stenosis [24] as well as limited coronary flow [23], and TAG may fail to detect stenosis that limits flow as assessed by invasive FFR during pharmacologic stress but does not reduce resting coronary flow. This underlying mechanism may also explain why the combination of TAG and CCTA stenosis did not provide a greater diagnostic performance over CCTA stenosis alone in the current study and the aforementioned study [20].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Therefore, abnormality by TAG is likely to be associated with severe anatomic stenosis [24] as well as limited coronary flow [23], and TAG may fail to detect stenosis that limits flow as assessed by invasive FFR during pharmacologic stress but does not reduce resting coronary flow. This underlying mechanism may also explain why the combination of TAG and CCTA stenosis did not provide a greater diagnostic performance over CCTA stenosis alone in the current study and the aforementioned study [20].…”
Section: Discussionmentioning
confidence: 62%
“…TAG is a novel method developed to assess the hemodynamic significance of CAD and is calculated using a linear regression model of luminal contrast attenuations in a coronary vessel obtained by manual or semi-automated techniques [9,10,[19][20][21][22]. To date, several studies have examined the relation of TAG to invasive FFR and have shown a variety in the diagnostic accuracy of TAG in predicting lesion-specific ischemia by invasive FFR \0.80.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…69 A subsequent comparison with invasive FFR revealed no incremental value for TAG (69% sensitivity, 44% specificity, 27% PPV, and 83% NPV) over CTA alone (95% sensitivity, 75% specificity, 54% PPV, and 98% NPV) in 253 vessels in 85 patients; the addition of CCO and exclusion of calcified segments only slightly improved the results. 70 Finally, in a 3 part study of phantoms, dogs and 152 vessels in 62 patients undergoing ICA, no significant TAG differences were noted between stenotic and normal vessels. Proximal to distal decreases in attenuation were a function of vessel diameter rather than stenosis.…”
Section: Ct Myocardial Perfusion Imagingmentioning
confidence: 93%